FORMATION OF A MODEL OF SUSTAINABLE ENTREPRENEURSHIP DEVELOPMENT IN THE CONDITIONS OF POST-WAR ECONOMIC RECOVERY OF UKRAINE - Дубіна, Микола І. (Journal of Strategic Economic Research, 2025)
The article presents the results of a study on the formation of a model of sustainable entrepreneurship development in the conditions of post-war economic recovery of Ukraine. It is substantiated that in the context of the post-war reconstruction of our state, a return to the traditional model of entrepreneurship, focused exclusively on profit maximization, is not only insufficient, but also strategically dangerous. Such an approach risks recreating old economic vulnerabilities and deepening social tension and environmental degradation caused by the war. It is proven that sustainable entrepreneurship development is becoming a necessary paradigm, which involves not only the reconstruction of destroyed facilities, but also the creation of business models based on the principles of a circular economy that recycle construction waste; the launch of social enterprises that ensure the reintegration of veterans and internally displaced persons; the development of innovative "green" technologies that strengthen energy independence and the resilience of communities. It has been established that the path to building a sustainable entrepreneurship ecosystem in Ukraine is extremely difficult. It is complicated by such factors as permanent security risks, destroyed logistics, lack of financial resources for small and medium-sized businesses, imperfect institutional environment and the absence of a holistic state policy aimed at stimulating sustainable business activities.